Rethinking Hindu Identity - Jha, D. N. (Dwijendra Narayan), 1940- (London : Equinox Publishing Ltd, 2009)
The book provides an antidote to the virulent version of Hindu communalism and cultural chauvinism and seeks to expose the hollowness of the xenophobic claims about Hindu religious identity. It identifies some of the stereotypes about Hinduism and shows them to be without any basis in historical evidence. Contrary to the belief popularized by the Hindu jingoists, it shows that Hinduism, far from being eternal and monolithic, is the youngest of religions and that its supposed tolerant nature is a myth.
Abbreviations -- Preface -- Introduction -- 1. Deconstructing Hindu identity -- 2. Tolerant Hinduism: evidence and stereotype -- 3. Holy cow: elusive identity -- Notes -- Bibliography -- Index.
Print version record.
Includes bibliographical references (pages 62-89) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Hinduism; Religion; Hinduism; Hinduismus; RELIGION / Comparative Religion; Electronic books